Method for extraction and identification of gelatin - Ismail, Amin; Che Man, Yaakob; Tukiran, Nur Azira; Mohd Amin, Aina; Raja Nhari, Raja Mohd Hafidz (2012)
The present invention generally relates to extraction and identification of gelatin. More particularly, the present invention relates to a method of extracting gelatin protein from collagen containing raw materials and identifying the source of the extracted gelatin protein, the method comprising the steps of extracting gelatin proteins using acetone solution and separating the extracted gelatin proteins to their molecular weights by way of gel electrophoresis, wherein the molecular weight difference of the proteins is used as a biomarker to identify the source of the extracted gelatin proteins.